Number Theory, Analysis, and Combinatorics: Proceedings of the Paul Turan Memorial Conference held August 22-26, 2011 in Budapest - Pintz, János; Biró, András; Györy, Kálmán; Harcos, Gergely; Simonovits, Miklós; Szabados, József (De Gruyter, 2013)
Paul Turán; Number Theory; Analysis Combinatorics